Characterization and radiation shielding efficiency of MWCNT/shape memory ternary blend composite films - Pekdemir, Sibel Selcuk; Yilmaz, Demet; Kuzu, Serpil Yalcin; Pekdemir, Mustafa Ersin (Pergamon-Elsevier Science Ltd, 2024)
In this study, the structural, X-ray and gamma-ray, and neutron shielding properties of shape memory ternary blend/multi-walled carbon nanotube (MWCNT) composite films were investigated. The composition of the composite films was defined as (100-x) poly (epsilon-caprolactone) (PCL):polyethylene glycol (PEG):polyvinyl chloride (PVC) + xMWCNT, where x = 0, 1, 3, 5% (mole percentage). The ternary blend/MWCNT composite films were characterized using Attenuated Total Reflectance Infrared Spectroscopy (ATR-IR), Thermogravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM). Thermal results showed that the degradation temperatures of composite materials with two degradation curves increased with increasing MWCNT percentage. The appearance of the MWCNT signal along with the characteristic polymer signals in the XRD pattern may be evidence that MWCNT is homogeneously distributed in the polymer blend. The mass attenuation coefficients (MAC), half-value layer (HVL), mean free path (MFP), and effective atomic numbers (Z_eff) of the composite films were experimentally measured over an energy range of 8.04-383.85 keV. Additionally, the equivalent dose rates for fast neutrons were measured, and the exposure buildup factor (EBF) and fast neutron removal cross-section (Sigma_R) were theoretically calculated. The proton and alpha shielding parameters of the ternary blend/MWCNT composite films were determined, revealing that the inclusion of higher amounts of MWCNTs in the composite structure significantly improved capability of the films in shielding against radiation and neutrons.
Keywords: Poly epsilon-caprolactone; Poly vinyl chloride; Radiation shielding; Neutron shielding; Shape memory ternary blend; MWCNT